INDICATORS AND MEASURE FOR ASSESSING FINANCIAL STABILITY OF THE PENSION SYSTEM (World Economics and Finance Bulletin, 2023)
This article presents information on criteria and indicators for measuring financial sustainability of pension system in Uzbekistan’s national economy; including factors determining the efficacy of pension system. It scrutinizes the priority goals to enable provision of pension funds to all level of nation, which includes amelioration of institutional framework, improvement of legislation in subsidies and optimization procedure in the allocation of pension amounts. Moreover, indicators that are presented in the article are separated in the following groups: senility level indicators, indicators characterizing the level of pension payments, efficiency indicators and financial stability indicators. Every indicator that is used in the measurement is presented with the description, formula as well as its brief explanation
Keywords: Pension system; Insurance premium; GDP; Financial stability